Development of an inter-confirmatory plastic characterization system using spectroscopic techniques for waste management. (1st August 2022) - Adarsh, U.K.; Bhoje Gowd, E.; Bankapur, Aseefhali; Kartha, V.B.; Chidangil, Santhosh; Unnikrishnan, V.K.
Graphical abstract: Highlights: Dual-spectroscopy to classify plastics based on elemental and molecular properties. LIBS-Raman techniques in single platform for reliable and cost-effective sorting. Classification of real-world plastics in industry-like environment. Classification capability evaluated using multivariate analysis. Abstract: Ever-accumulating amounts of plastic waste raises alarming concern over environmental and public health. A practical solution for addressing this threat is recycling, and the success of an industry-oriented plastic recycling system relies greatly on the accuracy of the waste sorting technique adapted. We propose a multi-modal spectroscopic sensor which combines laser-induced breakdown spectroscopy (LIBS) and Raman spectroscopy in a single optical platform for characterizing plastics based on elemental and molecular information to assist the plastic identification-sorting process in recycling industries. The unique geometry of the system makes it compact and cost-effective for dual spectroscopy. The performance of the system in classifying industrially important plastic classes counting PP, PC, PLA, Nylon-1 1, and PMMA is evaluated, followed by the application of the same in real-world plastics comprising PET, HDPE, and PP in different chemical-physical conditions where the system consumes less than 30 ms for acquiring LIBS-Raman signals. The evaluation of the system in characterizing commuting samples shows promising results to be applied in industrial conditions in future. The study on effect of physical–chemical conditions of plastic wastes in characterizing them using the system shows the necessity for combining multiple techniques together. The proposal is not to determine the paramount methodology to characterize and sort plastics, but to demonstrate the advantages of dual-spectroscopy sensors in such applications. The outcomes of the study suggest that the system developed herein has the potential of emerging as an industrial-level plastic waste sorting sensor.